(untitled) (Journal of Applied and Natural Science, 2015)
The aim of this work was to study the method to prepare the folk medicinal cream for the use of skin protection from the extracted substance of Indian almond leaves, Terminalia catappa L. in 4 periods as young green leaf , mature green leaf, orange red leaf and brown leaf by 4 methods. Tannic acid was the key index in preparation ,and tested by TLC and quantized its content. ?-carotene was also TLC test in quality check. The study showed that the brown leaves sample treated by heating at 100oC for 5 minutes and continue fermentation for 21 days, gave the extracted solution that contained highest tannic acid approximately as 80 mg/100g and was considered the best one. The extracted solution was used as one ingredient in folk cream. In this work, the four formulations with variation of extracted solution were studied and analysed total phenolic compound , tannic acid and antioxidant inhibition power. The cream with more extracted substance showed total phenolic compound , tannic acid more than those fewer content of extracted substance. This work found that the skin cream protection with antioxidation substance could made from extracted substance of Indian almond leaves.